Ancient DNA preservation, genetic diversity and biogeography: A study of houseflies from Roman Qasr Ibrim, lower Nubia, Egypt. (August 2020) - Simpson, A.; Fernández-Domínguez, E.; Panagiotakopulu, E.; Clapham, A.
Abstract: The optimal preservation of many Egyptian archaeological sites provides unique opportunities in the research into the evolution of synanthropic species, wild animals or plants, which benefit from close association with man-made human habitats. In this study we extracted and analysed ancient mitochondrial DNA (mtDNA) from three synanthropic insect species, two storage pests, Sitophilus granarius (Coleoptera: Curculionidae) (N = 8) and Trogoderma granarium (Coleoptera: Dermestidae) (N = 14), and the housefly Musca domestica (Diptera: Muscidae), (N = 14), from Roman Qasr Ibrim, an Egyptian frontier site located in lower Nubia. The impact of different experimental variables on ancient DNA recovery was also evaluated, confirming that it is possible to extract endogenous ancient DNA from desiccated specimens while preserving the insect exoskeleton. A phylogenetic comparison of the Qasr Ibrim housefly mtDNA-COI (COI) with modern housefly sequences, revealed that they were genetically similar to modern Egyptian, Near Eastern, Indian, Japanese, and US/Canadian populations. As the now cosmopolitan houseflies were transported by human populations alongside domestic animals and crops and may have aided the spread of disease, these findings provide important information for these processes. While limited by the resolution of the comparative databases, our research suggests the existence of biological invasions and links across the Red Sea from Egypt to the Arabian Peninsula, and exchanges between India and Egypt. We demonstrate the great potential of fossil insect aDNA for reconstructing biogeographic and diachronic species distribution and for better understanding past environments. Highlights: Ancient mitochondrial DNA successfully extracted from housefly,   Musca domestica, from Roman Qasr Ibrim, Lower Nubia, Egypt. Our results confirm that it is possible to extract DNA from ancient Diptera without morphological damage to the specimen. Our analysis revealed affinities between ancient and modern housefly populations from Egypt, Israel, Saudi Arabia and India. Our results could be explained through ancient trade routes, recent trade and the spread of houseflies globally. The study of synanthropic insect species can inform about human movement, trade and past environments.